MERETAS KEBEKUAN IJTIHAD DALAM ISU-ISU HUKUM ISLAM KONTEMPORER: IJTIHAD - Imam Makmun; Darussalam Syamsuddin; Kurniati (Al-Mizan (e-Journal), 2022)
This article describes contemporary problems that have been growing and are being asked to solve. This research is literature research with a casuistic approach and analyzed descriptively qualitatively. The results of the study show that a mujtahid must really study and review many legal issues decided and depending on the conditions and needs. Ijtihad is one of the methods of extracting Islamic law that logically and rationally in social change always tries to conduct research or experiments on increasing law in society, so it must be tested that the value of ijtihad can be justified by scientists and is objective. Ijtihad in issues of contemporary Islamic law is one method that makes Islamic law more dynamic and contextual in nature and not out of date.